Alexey Remizov and Boris Savinkov: A History of Relationship in Letters and Memoirs - Alla M. Gracheva (Studia Litterarum)
The article reveals a history of relations between A.M. Remizov and B.V. Savinkov from 1901 to 1924. Their friendly contacts that were established during their Vologda exile were temporarily interrupted by the struggle for the fate of Remizov’s bride, Serafima Dovgello. In the second half of the 1900s, Remizov acted as the maitre of the famous revolutionary and novice writer Savinkov. In the 1910s, their communication was interrupted. Savinkov and Remizov met in 1917 in Petrograd. They disagreed in their attitude towards October Revolution. Their last rapprochement took place in Paris in the early 1920s, when both were going through a difficult period of accommodation to the world of the Russian post-revolutionary emigration. After Savinkov’s death, his image repeatedly appeared in Remizov’s works of the 1925–1940s. The history of their relationship significantly complements the understanding of the parameters of Russian culture at the beginning of the twentieth century. The article is followed up by the first publication of the correspondence between Remizov and Savinkov and obscure memoirs of him by A.M. and S.P. Remizovs.